Evaluating the Relationship Between Participation in Student-Run Free Clinics and Changes in Empathy in Medical Students. (July 2017) - Modi, Anita; Fascelli, Michele; Daitch, Zachary; Hojat, Mohammadreza
Purpose: We explored differences in changes in medical student empathy in the third year of medical school between volunteers at JeffHOPE, a multisite medical student–run free clinic of Sidney Kimmel Medical College (SKMC), and nonvolunteers.Method: Volunteerism and leadership experience at JeffHOPE were documented for medical students in the Class of 2015 (n = 272) across their medical educations. Students completed the Jefferson Scale of Empathy at the beginning of medical school and at the end of the third year. Students who reported participation in other Jefferson-affiliated clinics (n = 44) were excluded from this study. Complete data were available for 188 SKMC students.Results: Forty-five percent of students (n = 85) volunteered at JeffHOPE at least once during their medical educations. Fifteen percent of students (n = 48) were selected for leadership positions involving weekly clinic participation. Nonvolunteers demonstrated significant decline in empathy in medical school ( P = 0.009), while those who volunteered at JeffHOPE at least once over the course of their medical educations did not show any significant decline ( P = 0.07).Conclusions: These findings suggest that medical students may benefit from volunteering at student-run free clinics to care for underserved populations throughout medical school.